In situ anticaries efficacy of dentifrices with different formulations – A pooled analysis of results from three randomized clinical trials. (October 2018) - Zero, Domenick T.; Lippert, Frank; Hara, Anderson T.; Creeth, Jonathan E.; Newby, Evelyn E.; Butler, Andrew; Constantin, Paul; Bosma, Mary Lynn
Abstract: Objectives: Data generated from three similar in situ caries crossover studies presented the opportunity to conduct a pooled analysis to investigate how dentifrice formulations with different fluoride salts and combinations at concentrations of 1400–1450 ppm F, different abrasive systems and in some cases, carbomer (Carb), affect enamel caries lesion remineralization and fluoridation. Methods: Subjects continuously wore modified partial dentures holding two gauze-covered partially-demineralized human enamel specimens for 14 days and brushed 2×/day with their assigned dentifrice: Study 1: sodium fluoride (NaF)/Carb/silica, NaF/silica, NaF + monofluorophosphate (MFP)/chalk; Study 2: NaF/Carb/silica, NaF + MFP/dical, amine fluoride (AmF)/silica; Study 3: NaF/Carb/silica, NaF + stannous fluoride (SnF2 )/silica/hexametaphosphate (HMP). All studies included Placebo (0 ppm F) and/or dose-response controls (675 ppm F as NaF [675F-NaF]) ±Carb. Specimens were evaluated for percentage surface microhardness recovery (SMHR) and enamel fluoride uptake (EFU). Results: All 1400–1450 ppm F dentifrices except NaF + SnF2 /silica/HMP provided significantly greater lesion remineralization than Placebo (p < 0.0001): differences in SMHR ranged from 17.46% (NaF + MFP/dical) to 26.66% (AmF/silica). For EFU (back-transformed log EFU), all 1400–1450 ppm F dentifrices gave significant fluoride uptake compared to Placebo (p < 0.0001): increases in EFU ranged from 4.95 μg F/cm 2 (NaF + SnF2 /silica/HMP) to 16.32 μg F/cm 2 (NaF/carb/silica). Dentifrices containing NaF or AmF as sole fluoride source provided the greatest remineralization and fluoridation; Carb addition did not alter fluoride efficacy; some excipients appeared to interfere with the cariostatic action of fluoride. Treatments were generally well-tolerated with ≤4 treatment-related adverse events per study. Conclusion: Commercially available fluoride dentifrices varied greatly in their ability to remineralize and fluoridate early caries lesions. Clinical significance: Fluoride dentifrices are the most impactful anticaries modality worldwide. While clinical caries trials have not consistently shown the superiority of one formulation over another, these findings using a sensitive in situ caries model indicated that dentifrices containing NaF or AmF as the sole fluoride source provided the greatest remineralization and fluoridation benefits.